Integration of landscape-level remote sensing and tree-level ecophysiology reveals drought refugia for a rare endemic, bigcone Douglas-fir - Post-Leon, Annapurna C.; Dryak, Mahalia; Zhu, Edward; De Guzman, Mark E.; Salladay, Ryan; Moritz, Max A.; Parkinson, Anne-Marie L.; Ramirez, Aaron R. (Frontiers in Forests and Global Change, 2022)
For forest species, areas buffered from the rapidly increasing climate stressors and patterns of disturbance — i.e., climate change refugia — are important targets for conservation and protection. Here, we present a novel field survey and remote sensing approach to identification of fine-scale functional drought refugia for bigcone Douglas-fir (Pseudotsuga macrocarpa)-dominated forests. This rare species has been exposed to climate change-exacerbated drought conditions over the past two decades; yet, little is known about its responses to recent drought and how these drought responses vary across local environmental gradients and interact with recent record wildfire seasons. We combined a remote sensing analysis of vegetation condition with field surveys and physiological measurements to better understand bigcone Douglas-fir responses to recent climate trends. We also identified 444 stands exhibiting relatively low response and high resilience to drought — i.e., potential drought refugia. We found that low elevation stands and those in south-facing aspects generally experienced greater levels of seasonal and interannual drought stress. This trend was more pronounced for stands that experienced fire (2007 Zaca Fire) prior to the drought, suggesting that wildfire can increase the importance of topographic mediation of climate conditions in bigcone Douglas-fir forests. Elevation and aspect also interacted to affect physiological acclimation to seasonal drought conditions, with low elevation north-facing sites in particular experiencing a favorable combination of greater climate buffering and greater drought resilience, suggesting that these sites may be important refugia for bigcone Douglas-fir at low elevations. Furthermore, we found that the relationships between topography and drought response were weaker in more coastal sites, possibly due to maritime climate buffering in these sites. Altogether, these results illustrate how topographic mediation of regional drought conditions is critical for persistence of rare species in drought and fire-prone landscapes, and offer important insights for the conservation and restoration of this iconic species.